ENDOPHYTIC FUNGI ISOLATED FROM MEDICINAL PLANT-A PROMISING SOURCE OF POTENTIAL BIOACTIVE METABOLITES. - G., Chathurdevi; Gowrie, S. Uma (International Journal of Current Pharmaceutical Research, 2016)
Objective: Medicinal plants are gaining worldwide attention owing to the fact that the herbal drugs are cost effective, easily available and with negligible side effects. Medicinal plants harbour endophytic microflora and they are valuable source of Bioprospecting endophytes. Endophytes are the microorganisms that inhabit interior of plant tissues that shows no apparent harm to host. Endophytic fungi from medicinal plants are known as Promising Sourceâ€ of bioactive novel metabolites which has significant role in pharmacology, agriculture and in industries. Methods: In our present research work, endophytic fungi were isolated from the leaves of medicinal plant Cardiospermum halicacabum. The frequency of the presence of endophytic fungi was studied based on seasonal variation. Seven endophytic fungi were isolated, of which two isolates were sporulating and identified based on colony morphology, sporulating structures and taken for further studies. The ethyl acetate extract of the isolates were screened for phytochemical studies and also assayed for invitro antibacterial activity. Further, the fungal isolates were checked for their ability to produce extracellular enzymes by qualitative assay and were used to study the presence of chitosan on their cell wall. Results: The isolates were also screened for extracellular biosynthesis of Silver nanoparticles for which UV-VIS absorption was recorded. FT-IR analysis was also performed to confirm the presence of various functional groups. Conclusion: The endophytes from Cardiospermum halicacabum can be a potent natural source of bioactive compounds which can be considered to be prolific resource for drugs and as Bioprotectants. Further investigation will focus on the strain improvement and genomic variation among these isolates.